Small ruminant production in Ethiopia: Constraints and future prospects - Awgichew, K.; Gebru, G.; Alemayehu, Z.; Akalework, N.; Fletcher, J. (Institute of Agricultural Research, 1991)
Summerizes the present situation, the constraints and the prospects of small ruminant production in Ethiopia; examines the past and current small ruminant research and Development on breed evaluation, management, marketing, health and the production of animal products; and discusses the biological and physical prospects for increasing sheep and goat production in the country.